Knowledge, attitudes, and practices of epilepsy patients regarding the ketogenic diet therapy: A cross‐sectional study - Xiuping Zhang; Meizhen Sun; Guofang Xue; Yongxiong Zhao; Taotao Du; Xueying Guan; Yong Xu (Epilepsia Open)
Abstract Objective The therapeutic ketogenic diet is typically used in epilepsy treatments, yet there has been insufficient understanding regarding the knowledge, attitudes, and practices (KAP) of epilepsy patients concerning this dietary therapy. This study aims to investigate the KAP of epilepsy patients regarding ketogenic diet therapy, with the goal of identifying gaps in knowledge and attitudes that may impact clinical outcomes. Method A cross‐sectional study was conducted between November 2023 and December 2023 at three epilepsy centers in Shanxi Province: the First Hospital of Shanxi Medical University, the Second Hospital of Shanxi Medical University, and Taiyuan Epilepsy Hospital. Data, including demographic characteristics and KAP scores, were collected via online questionnaires, yielding a total of 612 valid responses, with 320 (52.29%) males. Results The mean KAP scores were calculated as follows: knowledge score 4.99 ± 6.72 (possible range: 0–24), attitude score 24.82 ± 2.34 (possible range: 8–40), and practice score 29.48 ± 8.49 (possible range: 9–45). Multivariate analysis revealed that the attitude score (OR = 1.443, 95% CI: [1.296–1.607], p < 0.001) and an epilepsy duration of 5–10 years (OR = 3.086, 95% CI: [1.716–5.548], p < 0.001) were independently associated with positive practice. Additionally, Structural Equation Modeling indicated that knowledge (β = 0.034, p = 0.012) and attitude (β = 0.583, p = 0.010) directly influenced practice, while knowledge also directly affected attitude (β = 0.565, p = 0.013), with an indirect effect on practice through attitude (β = 0.329, p = 0.009). Significance The study found insufficient knowledge, suboptimal attitudes, and negative practices toward the ketogenic diet among epilepsy patients. This underscores the need for targeted educational interventions to enhance patient engagement and optimize clinical outcomes. Plain Language Summary This study looked at how much epilepsy patients know about, feel about, and use the ketogenic diet as a treatment. We found that patients generally know little about the diet, have mixed feelings, and do not use it much. Better understanding and positive attitudes were linked to better use of the diet. The results suggest that more education could help patients use the diet more effectively, which might improve their health outcomes.